Enhancing State Emergency Capacity through Digital Governance: Comparative Evidence from Earthquake Disaster Management in China and Japan - Medvedeva Nadezda; Artamonova Anastasiia (Indonesian Journal of Advanced Research, 2026)
The increasing frequency and complexity of natural disasters underscore the need for effective emergency governance and robust state capacity. Concurrently, rapid advances in digital technologies, including artificial intelligence (AI), big data analytics, geographic information systems (GIS), remote sensing, and early digital warning systems, have transformed global disaster management practices. Despite a growing literature on digital governance and emergency management, limited research examines how digital technologies enhance state emergency capacity through governance mechanisms. This study investigates the relationship between digital governance and state emergency capacity through a comparative analysis of earthquake management in China and Japan. The analysis focuses on four major earthquake events: the Wenchuan Earthquake (2008), the Luding Earthquake (2022), the Great East Japan Earthquake (2011), and the Noto Peninsula Earthquake (2024). The findings indicate that digital technologies do not directly improve disaster management outcomes. Instead, they strengthen information-gathering, coordination, resource mobilization, and implementation capacities through digital government infrastructures and digital governance mechanisms. While China demonstrates advantages in centralized coordination and large-scale resource mobilization, Japan excels in automated warning systems and public preparedness. The article contributes to the literature by identifying state capacity as the key mediating variable between digital transformation and emergency management performance, and proposes an integrated digital emergency governance model for future disaster management.